Prifacounter: The innovation of traffic counter application for android OS - J. Romadhona, Prima; Chasanah, Faizul (International Journal of Engineering and Technology, 2018)
In civil engineering, particularly in the field of traffic engineering, it was possible to measure traffic performance by way of surveying the traffic flow, velocity, and density. The current traffic survey is commonly conducted by surveyor who manually calculates the movement of mode of transportation using traffic counter and survey form. Such method was definitely way too costly and time consuming in rendering the traffic data. Therefore, this study aims was to create application design products for technology retrieval and vehicle traffic count calculations, as well as traffic behavior analysis. This research was used Research and Development (R & D) method. The data accuracy was maintained through check and control to make sure that the inputted data were precisely the same with the results of the display on the application. This application called PRIFACOUNTER that can be operated personally in android OS hand phone. On the basis of the research, it was revealed that some variables and steps in the application concept were definitely needed to determine traffic behavior consisting of traffic flow, capacity, and degree of saturation. Since anyone can use this application, it will reduce the time in order to analyze the traffic performance.Â Â